The social life of standards ethnographic methods for local engagement - Graham, Janice Elizabeth 1958-; Holmes, Christina 1973-; MacDonald, Fiona; Darnell, Regna 1943- (UBC Press, 2021)
"Through twelve ethnographic case studies, The Social Life of Standards reveals how standards – political and technical tools for organizing society – are developed, applied, subverted, contested, and reassembled by local communities interacting with norms often created by others. Contributors explore standards at work across different countries and contexts, such as Ebola biomedical safety precautions in Senegal, Colombian farmers contesting politicized seed regulations, and the application of Indigenous standards to Canadian environmental assessments. They emphasize the uncomfortable fit between the often messy and inconsistent implementation of standards in the real world and the monolithic, non-negotiable criteria presupposed by external forces. Overt conflict arises when standards misrepresent important local (or global) realities. How do communities actively challenge and re-create standards that do not meet their needs? The Social Life of Standards provides an important anthropological perspective on the articulation of standards. The goal is to arrive at a more reflexive process that offers progressive engagement at the local level. Ultimately, we need an effective balance between evidence-based science, the social contexts that inform more useful and appropriate standards, and the inherent potential for activism."--